Respostas

2013-01-08T19:09:28-02:00

b)p(x)+6q(x) pois é o resultado final somado e mutiplicado !

  • Usuário do Brainly
2013-01-08T19:19:31-02:00

Conforme o enunciado, temos:

 

\text{p}(\text{x})=4\text{x}^3-\text{x}^2+10\text{x}+2

 

E, também:

 

\text{q}(\text{x})=3\text{x}^2+15\text{x}+4

 

Desta maneira, tém-se:

 

a)

 

\text{p}(\text{x})+\text{q}(\text{x})=(4\text{x}^3-\text{x}^2+10\text{x}+2)+(3\text{x}^2+15\text{x}+4)

 

=4\text{x}^3+2\text{x}^2+25\text{x}+6

 

Analogamente, temos:

 

b)

 

\text{p}(\text{x})+6\cdot\text{q}(\text{x})=(4\text{x}^3-\text{x}^2+10\text{x}+2)+6\cdot(3\text{x}^2+15\text{x}+4)

 

=(4\text{x}^3-\text{x}^2+10\text{x}+2)+(18\text{x}^2+90\text{x}+24)

 

=4\text{x}^3+17\text{x}^2+100\text{x}+26